Small-Scale Hydropower and Energy Recovery Interventions: Management, Optimization Processes and Hydraulic Machines Applications - Rossi, Mosè; Renzi, Massimiliano; Štefan, David; Muntean, Sebastian (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Several topics in the small-scale hydropower sector are of great interest for pursuing the goal of a more sustainable relationship with the environment. The goal of this Special Issue entitled "Small-Scale Hydropower and Energy Recovery Interventions: Management, Optimization Processes and Hydraulic Machines Applications" was to collect the most important contributions from experts in this research field and to arouse interest in the scientific community towards a better understanding of what might be the main key aspects of the future hydropower sector. Indeed, the Guest Editors are confident that the Special Issue will have an important impact on the entire scientific community working in this research field that is currently facing important changes in paradigm to achieve the goal of net-zero emissions in both the energy and water sectors.